2004
DOI: 10.1038/nature02179
|View full text |Cite
|
Sign up to set email alerts
|

Natural examples of olivine lattice preferred orientation patterns with a flow-normal a-axis maximum

Abstract: Tectonic plate motion is thought to cause solid-state plastic flow within the underlying upper mantle and accordingly lead to the development of a lattice preferred orientation of the constituent olivine crystals. The mechanical anisotropy that results from such preferred orientation typically produces a direction of maximum seismic wave velocity parallel to the plate motion direction. This has been explained by the existence of an olivine preferred orientation with an 'a-axis' maximum parallel to the induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
82
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(98 citation statements)
references
References 21 publications
15
82
0
1
Order By: Relevance
“…Recently, Katayama [2009] argued that the seismic anisotropy induced by olivine fabrics could result from a thin layer along the slab and overriding plate. Whereas the olivine fabrics may be B-type along the slab as documented by Mizukami et al [2004], Skemer et al [2006], and Tasaka et al [2008], our results argue that the seismic properties induced by B-type fabrics along the slab are counteracted by those induced by a-axis slip olivine fabrics in the uppermost mantle of the overriding plate beneath the volcanic front (Figure 3), as the two slip systems produce similar degrees of rock seismic anisotropy (compare Figure 2 with Tasaka et al [2008]). Therefore, other factors such as melt alignment in the low-velocity zone or cracks with fluid infill might represent the more likely explanation of the observed seismic anisotropy in the vicinity of the volcanic front.…”
Section: Discussionmentioning
confidence: 63%
“…Recently, Katayama [2009] argued that the seismic anisotropy induced by olivine fabrics could result from a thin layer along the slab and overriding plate. Whereas the olivine fabrics may be B-type along the slab as documented by Mizukami et al [2004], Skemer et al [2006], and Tasaka et al [2008], our results argue that the seismic properties induced by B-type fabrics along the slab are counteracted by those induced by a-axis slip olivine fabrics in the uppermost mantle of the overriding plate beneath the volcanic front (Figure 3), as the two slip systems produce similar degrees of rock seismic anisotropy (compare Figure 2 with Tasaka et al [2008]). Therefore, other factors such as melt alignment in the low-velocity zone or cracks with fluid infill might represent the more likely explanation of the observed seismic anisotropy in the vicinity of the volcanic front.…”
Section: Discussionmentioning
confidence: 63%
“…Karato et al (2008) suggested that that the asthenospheric upper mantle may generally be dominated by E-or C-type olivine rather than the traditionally assumed A-type. Natural occurrences of each of the olivine fabric types recognized in the laboratory have been identified, notably B-type fabric from convergent boundaries (e.g., Mizukami et al 2004;Skemer et al 2006) and C-type fabric from deep mantle samples (see, e.g., Katayama and Karato 2006). However, global databases of fabric types for natural peridotite samples (Ben Ismail and Mainprice 1998) show that B-, C-, and E-type fabrics make up very small percentages of the global population (approximately 7, 7, and 2%, respectively; Mainprice 2007), and most samples are A-or D-type.…”
Section: The Upper Mantlementioning
confidence: 99%
“…This hypothesis for subduction zone anisotropy originated with Jung and Karato (2001), who conducted laboratory experiments on olivine aggregates with significant water content (200-1200 ppm) deformed at high differential stresses (>300 MPa) and found that slip along the [0 0 1] direction was enhanced at these conditions, such that the fast axes of individual olivine crystals tended to be aligned 90 • from the shear direction. Examples of Btype fabric in mantle-derived rocks have since been documented by Mizukami et al (2004) in samples from the Higashi-akaishi peridotite body in southwest Japan, just northeast of the Ryukyu arc. Subsequent modeling work by Kneller et al (2005) indicates that B-type fabric conditions may occur in part of the mantle wedge.…”
Section: Corner Flow With B-type Olivine Fabricmentioning
confidence: 99%